The European Second Generation Compared 2012
DOI: 10.1515/9789048516926-006
|View full text |Cite
|
Sign up to set email alerts
|

5 School careers of second-generation youth in Europe. Which education systems provide the best chances for success?

Abstract: The TIES respondents and their parents: Background socio-demographic characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 14 publications
0
15
0
4
Order By: Relevance
“…Previous studies revealed not only the importance of school structures in facilitating or hampering educational mobility (Crul et al 2012b), but that outside-family networks can also provide important additional resources for upward mobility (Gibson et al 2004;Meunier 2011) and for children from disadvantaged backgrounds and immigrant origin in particular (Cherng et al 2013;Schnell 2014).…”
Section: Outside the Family Homementioning
confidence: 99%
“…Previous studies revealed not only the importance of school structures in facilitating or hampering educational mobility (Crul et al 2012b), but that outside-family networks can also provide important additional resources for upward mobility (Gibson et al 2004;Meunier 2011) and for children from disadvantaged backgrounds and immigrant origin in particular (Cherng et al 2013;Schnell 2014).…”
Section: Outside the Family Homementioning
confidence: 99%
“…Mipex is concentrated on national policies; likewise, the data on social exclusion which this article examined are distinct on a national basis. But we know that the dynamics of integration are subject to extreme variability at the local level, both in the policies that accompany these dynamics (Alexander, 2007;Caponio and Borkert, 2010;Scholten and Penninx, 2016) and in the results that follow (Crul et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if higher credentials have a positive long-term effect on the labour market outcomes of immigrants and natives alike, as well as on their children's school performances (Heath et al, 2008;Alba and Holdaway, 2013;Ichou, 2014), migrants' educational and professional qualifications are not easily recognized in the host country. Moreover, the educational achievements of second generations vary greatly depending on the context (Crul et al, 2012;Heath and Brinbaum, 2014). The overall drop-out rate from compulsory schooling in the EU is equal to 14 per cent; the rate for second-country nationals is much higher (25 per cent), whereas for third-country citizens it rises to 34 per cent.…”
Section: A Preliminary Review Of the Immigrant Gap In The Eumentioning
confidence: 99%
“…En outre, bien qu'une grande partie arrive à terminer la scolarité secondaire en raison de son caractère obligatoire, ces jeunes sont vite mis au défi par la sélection au secondaire qui freine leurs ambitions scolaires (BAUM & FLORES, 2011 ;GRIGA & HADJAR, 2013). La sélection précoce dans certains pays est telle que seule une petite minorité est admise dans des filières ou programmes de formation générale conduisant à l'enseignement supérieur, tandis que la majorité est affectée dans des filières professionnelles de type court conduisant au marché du travail et la contraignant à mettre fin à la scolarité (CRUL et al, 2012).…”
Section: Les Parcours Scolaires Des Jeunes Canadiens D'origine Immigrunclassified